Pengaruh Pemberian Psycoeducation terhadap Kemampuan Adaptasi Sosial pada Mahasiswa Angkatan 2024 di Program Studi Diploma Tiga Keperawatan Universitas Abulyatama - Tanisya Ayudya; Urip Pratama; Nurul Amna (Pusat Riset dan Inovasi Nasional, 2025)
The first year of college is a critical transition period that can affect students’ motivation, stress levels, and risk of dropping out. This study aimed to determine the effect of psycho-education focusing on self-awareness on the social adaptability of 2024 Diploma III Nursing students. A quantitative quasi-experimental design with a one-group pretest-posttest approach was applied. The population consisted of 190 students, with 20 participants selected through purposive random sampling. The intervention involved eight 60-minute psycho-educational sessions designed to help students recognize, understand, and reflect on their emotions, thoughts, and behaviors in social contexts. The program was conducted from March 28 to May 3, 2025. Social adaptation was measured using the SACQ questionnaire, which demonstrated high reliability (Cronbach’s Alpha = 0.877). Results from the paired t-test revealed a significant difference between pretest and posttest scores, with a p-value of 0.000 (p < 0.05) and an average score increase of -12.050. These findings indicate that self-awareness interventions positively influence social adaptability, enabling first-year students to build relationships, adjust to new cultures, and face academic and social challenges more effectively. The study recommends implementing psycho-education programs as part of campus initiatives to strengthen social adaptation skills and provide preventive support for first-year students.